(untitled) (Ágora de Heterodoxias, 2026)
The aim of this study was to examine the association between sexist attitudes and victimization in intimate relationships among Mexican and Peruvian participants. Quantitative, descriptive, cross-sectional study. 452 individuals (aged 18 to 25) participated, including 262 Mexicans and 190 Peruvians. Two instruments were administered: the Ambivalent Sexism Inventory and the Violence Inventory. A multivariate analysis was conducted to identify clusters. The analysis of intimate partner violence revealed that Mexican participants were grouped into three clusters: non-victims, victims of emotional aggression, and victims of all types of aggression. Peruvian participants were grouped into: victims of all types of aggression, victims of jealousy-related aggression, and non-victims. Regarding sexism, Mexican participants were classified into the following groups: rejection of sexism, need for protection, and acceptance of sexism. Peruvian participants were classified into: need for protection, low disagreement with sexism, rejection of sexism, and acceptance of sexism. The association between intimate partner violence and sexism, analyzed through the chi-square test (χ²), showed that individuals who reject sexist beliefs are not victimized, whereas those who identify with sexist beliefs are at greater risk of experiencing all forms of aggression. It is concluded that sexist beliefs constitute a determining factor in violent intimate relationships.